(untitled) (Baghdad Science Journal, 2011)
Forty one isolates of genus Proteus were collected from 140 clinical specimens such as urine, stool, wound, burn, and ear swabs from patients of both sex. These isolates were identified to three Proteus spp. P. mirabilis, P. vulgaris and P. penneri .The ability of these bacteria to produce L-asparaginase II by using semi quantitative and quantitative methods was determined. P. vulgaris Pv.U.92 was distinguished for high level of L-asparaginase II production with specific activity 1.97 U/mg. Optimum conditions for enzyme production were determined; D medium with 0.3% of L-asparagine at pH 7.5 with temperature degree 35°C for incubation. Ultrasonication was used to destroy the P. vulgaris Pv.U.92 cells then ASNase II was extracted and purified throughout several purification steps including precipitation with (NH4)2SO4(60-80%), DEAE-cellulose ion exchanger chromatography followed by Sephacryl S-300 filtration. The specific activity was 155.6 U/ mg and the purification fold was 27.3 with 10.4% yield.